Investigating the implementation of teambased learning in a university level teacher education course - Abd.Samad, Arshad; Md. Rashid, Juridah; Syd Abd. Rahman, Sharifah Zainab; Hussein, Hawanum (Asian Economic and Social Society, 2014)
Team based learning is a popular educational approach in medical and business education, but is less common in other disciplines. This paper first compares team based learning to other similar approaches such as collaborative learning and cooperative learning that have gained a fairly strong following in the teaching of various disciplines. Secondly, it reports on the progress of a year-long research project that examined university student diary entries and questionnaire responses regarding the implementation of team based learning in a teacher-education context. Finally, it will propose rubrics for implementing team based learning at Malaysian institutions of higher education based on student responses received during the project.